Assessment of an Aujeszky's Disease Control Strategy in a Highly Prevalent Pig Farm Based on Systematic Vaccination With an Inactivated gE-Negative Marker Vaccine - Aznar, María N.; Bessone, Fernando A.; Segurado, Rodrigo; Duffy, Sergio J. (Frontiers in Veterinary Science, 2022)
Aujeszky’s Disease (AD) is endemic in Argentina. In 2016, an inactivated gE- negative marker Bartha K61 vaccine (AUSKIPRA® BK) started to be used, being the only country that carries out a control strategy plan with it. In the present article we describe the results of a control program in a farrow-to-finishing farm with high initial AD prevalence (33.0% in sows), based on systematic vaccination, detection and elimination of seropositive pigs, replacement of sows with vaccinated gilts and instauration of artificial insemination. The program was suitable for diminishing the incidence and the prevalence to levels compatible to virus eradication. This situation has been sustained over time. This is the first report of AUSKIPRA® BK efficacy under field conditions.